The application of artificial intelligence in language acquisition and instructional methodologies. - Makhsudova, Nargiza (The Lingua Spectrum, 2024)
This article delves into the transformative role of artificial intelligence (AI) in language learning and teaching methodologies. It highlights the various AI tools available, such as intelligent tutoring systems, language processing applications, and adaptive learning platforms, which tailor educational experiences to individual learner needs. The advantages of these technologies include increased learner engagement, personalized feedback, and the ability to analyze performance data to inform instructional strategies. Furthermore, the article examines how AI enhances traditional teaching methods, fostering a more interactive and immersive learning environment. By integrating AI into language education, educators can implement innovative strategies that cater to diverse learning styles and improve overall language proficiency. The effectiveness of these AI-enhanced methodologies is analyzed through case studies and empirical research, demonstrating significant improvements in learner outcomes. Ultimately, the article advocates for the broader adoption of AI in language education to maximize its potential and address the challenges faced by both learners and educators.